2023
DOI: 10.3390/cancers15153918
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Photodynamic Therapy in Gliomas

Abstract: Over the last 20 years, gliomas have made up over 89% of malignant CNS tumor cases in the American population (NIH SEER). Within this, glioblastoma is the most common subtype, comprising 57% of all glioma cases. Being highly aggressive, this deadly disease is known for its high genetic and phenotypic heterogeneity, rendering a complicated disease course. The current standard of care consists of maximally safe tumor resection concurrent with chemoradiotherapy. However, despite advances in technology and therape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 244 publications
0
6
0
Order By: Relevance
“…The influence of both first and second generation photosensitizers was tested. Most studies have confirmed the significant effectiveness of the therapy, but further studies are necessary to better define the effectiveness of PDT ( 116 , 236 , 237 ). In Germany, in 2007, Stepp et al.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The influence of both first and second generation photosensitizers was tested. Most studies have confirmed the significant effectiveness of the therapy, but further studies are necessary to better define the effectiveness of PDT ( 116 , 236 , 237 ). In Germany, in 2007, Stepp et al.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Protoporphyrin IX (PpIX) and fluorescein are most widely used as PS and as SS due to their safety profile and selective accumulation in tumor cells, and most studies in glioma use 5-aminolevulinic acid (5-ALA) as a precursor of PpIX [ 1031 , 1032 , 1033 ]. After surgery and adjuvant treatment, the residual tumor is predominantly comprised of resistant GSC clones; thus, several strategies have attempted to enhance 5-ALA uptake by this type of cells in order to increase the efficacy of PDT and SDT [ 1032 , 1033 ]. Moreover, iron chelators, such as deferoxamine and CP94, and ABC transporter inhibitors have been shown to increase PpIX levels in GB cells when utilized as adjuvants [ 1034 , 1035 ].…”
Section: Non-ionizing Energies In Gb Therapymentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a newly developed strategy for disease diagnosis and treatment using photodynamic effects . When photosensitizers were triggered and activated by laser in a given wavelength, the local reactive oxygen species (ROS) would increase and destroy the cell structure such as cell membrane, protein and even nucleic acids . This method has a different mechanism than traditional antibiotics, which enables antibiotic resistance could be controlled in a new way .…”
Section: Introductionmentioning
confidence: 99%
“… 2 When photosensitizers were triggered and activated by laser in a given wavelength, the local reactive oxygen species (ROS) would increase and destroy the cell structure such as cell membrane, protein and even nucleic acids. 3 This method has a different mechanism than traditional antibiotics, which enables antibiotic resistance could be controlled in a new way. 4 It is well-known that PDT processes advantages such as fewer side effects and localized treatment.…”
Section: Introductionmentioning
confidence: 99%